Judas Maccabeus and the Roman Republic: Greek Political Vocabulary in 1 Macc 8:1 - Nawrot, Janusz (Verbum Vitae, 2021)
The literary genius of the author of the First Book of the Maccabees shows in his ability to use the diplomatic realities of politics in the account of Judas Maccabeus, who strives to sign a pact with the Roman republic. The terms to describe politics have their own long history that dates back to the Greek world before Rome reached its prime. The use of these terms to represent Judas’ policy towards Rome in 1 Macc 8:1 was not an artificial ingenuity of the author but rather his intentional borrowing. By utilising terms from the spheres of politics and diplomacy, the author was capable of matching them with the everlasting value of the message contained in the inspired text. This message was extremely important for the author. Thus he was able to harmonise elements of world politics with God’s action. The Lord would use everything made by humans to exercise His will toward His own people.